Innovations in the teaching-learning process of psychiatric nursing and mental health - Claudia Mara de Melo Tavares; Américo de Araujo Pastor Junior; Laís Mariano de Paiva; Thainá Oliveira Lima (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to know innovative pedagogical experiences developed by professors in the teaching of psychiatric nursing and mental health in undergraduate nursing courses at public universities in Rio de Janeiro State. Method: based on an ethnomethodological approach, individual semi-structured interviews and document analysis were carried out according to content analysis. Results: despite the heterogeneity in the curriculum distribution of psychiatric nursing's and mental health's knowledge, the themes taught have similarities. The perceptions of innovation are mainly related to interdisciplinary practices and teaching, relational, and care technologies. Innovative teaching practices are focused on the use of active methodologies and collaborative activities. Final considerations: innovating teaching requires creating strategies to teach people how to care for people, valuing human uniqueness. Student participation in health services is the key to the dialogue between knowledge produced in academia and that mobilized in health services.